Integralidade no cuidado ao adolescente na atenção primária à saúde - Barreto, Camila Nunes (2023)
Introduction: adolescence is a singular stage in development, adolescents deal with the intensification of physical, mental, emotional, sexual and social transformations. The role of Primary Health Care (PHC) in comprehensive care for adolescents is highlighted, considering their needs and the particularities of the territory. Objectives: the objective was to analyze the health needs of adolescents from their perspective and that of health professionals and knowing the limits and possibilities in assistance of adolescents in primary health care. Method: Qualitative research, a descriptive, exploratory, developed in PHC health units and public state schools in a Health Region in the hinterland of Rio Grande do Sul. 24 health professionals and 12 adolescents participated through semi-structured interviews. Data were submitted to inductive thematic analysis. To interpret the results, the theoretical frameworks of the essential and derived attributes of Bárbara Starfield's PHC were used, and the Freirean theory. Study protocol Approved by the Ethics Committee on Human Research of the institution under opinion number 4,827,966. Results: The results showed that comprehensive care for adolescents involves recognizing the emotions and feelings expressed by them in the face of vulnerabilities, as well as identifying protective factors for their development. A look at family dynamics and social relationships stands out. Risk factors in the family scope are: parental unemployment, precarious economic conditions, structural machismo, unstable family ties, prejudice and stigmas related to adolescence and weakness of maternal and paternal figures. Considering the adolescents' feelings and desires, their autonomy, dialogue free of prejudice and punishment are positive for approaching this group, and as a result, an increase in bonding and security in relation to the team. However, PHC is not seen as a reference for care, nor do professionals feel prepared to care for adolescents. Although access to PHC by adolescents occurs, it is reduced compared to the other stages of the life cycle. The school stands out as a potential space for linking them to health services. The adolescents' life project is dynamic, and part of a continuous construction and reconstruction of their trajectory, based on experiences, values and identifications. Final considerations: the limits in the training of health professionals denote the importance of revising curriculum matrices. The importance of associating care with the use of technologies, social media and spaces frequented by adolescents stands out; the articulation between the APS and the Psychosocial Care Network. It is believed to strengthen the actions of PHC professionals, including practices consistent with their real needs, taking into account changes in the contemporary world, the impact of the pandemic and the relationships that adolescents establish and their influence on their development.